ACCOUNTING AND TAXATION IN JOINT-STOCK COMPANIES UNDER LEGISLATION CHANGES - Hura, Nadiya (Bulletin of Taras Shevchenko National University of Kyiv. Economics, 2023)
In this article, we discuss the methods, problems, and legal foundations of accounting and taxation of joint-stock companies in Ukraine. The law "On joint-stock companies" was passed in Ukraine in 2023, which caused certain changes in accounting in them. Also in this article, we explored the genesis of the legal foundations and their effect on the accounting in joint-stock companies, as well as such specific aspects as the accounting of the equity capital, the accounting and taxation of the dividends, and the financial reporting of stock profits. A comparative analysis of the legal foundations of joint-stock companies and accounting in them in Ukraine and foreign countries led to the conclusion that the main differences are: only shares with nominal value can be issued in Ukraine, dividends must be paid with money, dividends can't be reinvested into the equity capital. We offer examples of the accounting of establishment of the equity capital, increasing the equity capital through the issuance of extra shares, increasing the nominal value of shares and repurchasing of convertible bonds, as well as reduction of the equity capital through share cancellation or decreasing their nominal value, repurchasing and reselling shares at various prices, conversion of the preferred shares into common shares. We also demonstrated the features of the taxation and accounting of dividends for individuals and legal entities, as well as the calculation, accounting, and financial reporting of share profitability while showing the effects of the dilution of the common shares. In this article, particular changes to the regulatory documents of joint-stock companies are offered to put them in compliance with the recent changes in the law. General scientific methods such as dialectic, systemic, analysis and synthesis, induction and deduction, comparative method, as well as double-entry bookkeeping, which is specific to accounting, were used in this article.
Keywords: joint-stock companies; accounting and taxation; capital net worth; shares